2014
DOI: 10.1016/j.jbiotec.2014.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Stable overexpression of miR-17 enhances recombinant protein production of CHO cells

Abstract: HighlightsTransient overexpression of miR-17 and miR-17–92 cluster enhanced growth rate.Biological effects of long term and stable overexpression of miRNAs in batch cultures were studied.Stable miR-17 engineered CHO cells had both improved growth rate and productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 46 publications
0
66
0
Order By: Relevance
“…Subsequent studies were focused on providing insights into the importance of miRNAs for molecular pathways relevant to cell culture engineering, such as growth (Jadhav et al, 2014), apoptosis (Druz et al, 2011), and protein secretion (Barron et al, 2011; Loh et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies were focused on providing insights into the importance of miRNAs for molecular pathways relevant to cell culture engineering, such as growth (Jadhav et al, 2014), apoptosis (Druz et al, 2011), and protein secretion (Barron et al, 2011; Loh et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Jadhav V et al reported a similar result and designed an experiment to explain this phenomenon [34]. Their results demonstrated that transient positive effects on growth could also be observed during early exponential culture.…”
Section: Discussionmentioning
confidence: 76%
“…From these five, miR-2110 is a novel miRNA that has been identified but not studied (Zhu et al 2009). The other four miRNAs (miR-429, miR-18a-5p, miR-22-5p and miR-22-3p) have been associated with cancer research in which they have exhibited contradicting effects on cell proliferation, cell growth, and protein production depending on the cell type and stage of cell development (Jadhav et al 2014; Lang et al 2014; Liu et al 2014; Song et al 2013; Song et al 2014; Takakura et al 2008; Xiong et al 2010). For example, miR-429, a member of the miR-200 family, was shown to suppress tumor growth in human osteosarcoma(Liu et al 2014), while in non-small cell lung cancer (NSCLC), the same miRNA is suggested as a potential target for NSCLC due to its promotion of cell proliferation(Lang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This miR-17-92 cluster was studied in depth regarding its effect on recombinant EpoFc protein production in CHO cells. Although over-expression of the entire cluster decreased productivity while having no effect on cell growth, the over-expression of miR-17 and miR-92 were shown to increase production(Jadhav et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation